Trauma center proliferation in the United States: concerns and potential solutions - Niloofar Dehghan, MD; Lisa K. Cannada, MD; Ashraf N. El Naga, MD; Anna Miller, MD; Dan Schlatterer, DO; on behalf of the Orthopaedic Trauma Association Health Policy Committee (OTA International)
Abstract. There has been an increase in the number of Level I and II trauma centers across the United States in the past few decades. However, data suggest that access to trauma care remains poor in rural areas of the country, while in many urban areas, trauma center density may be too high. Excessive trauma center proliferation in urban areas has the potential for negative effects on patient care and increased trauma system costs. The efficiency and competency of each trauma center may be decreased by having less access to patients, with research, surgeon experience, and training programs for residents, fellows, medical students, and other allied health providers all affected. Because of these concerns, the Orthopaedic Trauma Association (OTA) Health Policy Committee reviewed trauma center trends and trauma system needs and considered the potential effect of the increase in the number of centers on patient care as well as surgeon experience and training. This article reviews the different types of trauma centers and their designation process, as well as the growth in trauma centers during the past few decades. The committee identified and explored each of these issues and provides suggestions for improvement. Potential solutions identified include developing and applying strict criteria for determining the number of trauma centers needed within a given region, considering the needs of the local population, cost containment, and impact on adjacent trauma centers and their educational and research missions. There is opportunity for the OTA to work even more collaboratively with the American College of Surgeons to develop such criteria and to be involved with the orthopaedic accreditation and orthopaedic requirements. Collaboration between professional medical societies such as the OTA and American College of Surgeons and state and federal agencies is needed to help optimize the distribution of trauma centers.